2003
DOI: 10.1002/anie.200351886
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Unique ansa‐Metallocene Framework by Intramolecular Photochemical [2+2] Cycloaddition of Bis(2‐alkenylindenyl)zirconium Complexes

Abstract: Developing the chemistry of organic functional groups on bent Group 4 metallocene frameworks and related systems has been notoriously difficult due to the high sensitivity of such organometallic compounds toward the typical reaction conditions used.[1] Noteworthy examples include a Mannichtype carbon-carbon coupling reaction [2] and selective transformations of olefinic substituents attached to the metallocene cyclopentadienyl rings, such as metallacyclic olefin coupling [3] and olefin metathesis reactions.[4]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 33 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…The Erker group employed this concept for the synthesis of novel ansa -metallocenes. 170 172 The bis(2-alkenylindenyl)zirconium complex 69 for example gave upon direct excitation the cyclobutylene-bridged zirconocene 70 in a yield of 50% ( Scheme 24 ). 170 A related behavior was observed for alkenyl-substituted lithium cyclopentadienides.…”
Section: Direct Excitation and Sensitizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Erker group employed this concept for the synthesis of novel ansa -metallocenes. 170 172 The bis(2-alkenylindenyl)zirconium complex 69 for example gave upon direct excitation the cyclobutylene-bridged zirconocene 70 in a yield of 50% ( Scheme 24 ). 170 A related behavior was observed for alkenyl-substituted lithium cyclopentadienides.…”
Section: Direct Excitation and Sensitizationmentioning
confidence: 99%
“… 170 172 The bis(2-alkenylindenyl)zirconium complex 69 for example gave upon direct excitation the cyclobutylene-bridged zirconocene 70 in a yield of 50% ( Scheme 24 ). 170 A related behavior was observed for alkenyl-substituted lithium cyclopentadienides. 173 Even a ladderane structure could be generated by employing a bis(butadienylcyclopentadienyl)zirconium complex.…”
Section: Direct Excitation and Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this specific reaction was not synthetically useful for a clean ansa-metallocene catalyst development because of its reversibility under the photochemical conditions to result in a photostationary equilibrium mixture of the open and closed isomers of most investigated examples under practical conditions (23, 24). We later showed that the [2-(1-methylethenyl)indenyl] 2 ZrCl 2 derivative (3) rapidly and completely underwent the intramolecular photolytic [2ϩ2]cycloaddition reaction when irradiated with Pyrex-filtered light to yield 4, from which an interesting homogeneous metallocene ZieglerNatta catalyst system was generated (25)(26)(27)(28). This posed the question as to whether the outcome of the intramolecular [2ϩ2]photocyclization reaction at the group 4 bent metallocenes might significantly depend on the substituent at the alkenyl functional group and that the use of, e.g., the 1-methylalkenyl moiety might actually lead to a synthetically favorable situation.…”
mentioning
confidence: 99%
“…In 2004, Erker et al reported an interesting ansa-metallocene framework 126 through the intramolecular [2+2] photocycloaddition of a bis(2-alkenylindenyl)zirconium complex 125. 69…”
Section: Scheme 31 Olefin Cycloaddition In the Total Synthesis Of Rhododaurichromanic Acidsmentioning
confidence: 99%